Acrylic resin disinfection by peracetic acid and microwave energy - FORTES,Carmen Beatriz Borges (2015)
Objective: The objective of this study was to evaluate the effectiveness of disinfection methods in microwave and immersion in peracetic acid in heat-cured, self-cured and microwave-cured acrylic resin, contaminated with Candida albicans. Methods: Five specimens were prepared for each type of acrylic resin. All were infected with Candida Albicans, incubated at 37°C for 24 hours. The group which underwent microwave energy was irradiated with a power of 840W for 1 minute and the other group underwent disinfection by soaking of 0.2% peracetic acid for 5 minutes. Results: All samples proved to be contaminated after the incubation period. After the different processes of disinfection, both immersion in 0.2% peracetic acid as microwave irradiation were effective in disinfection of the 3 types of acrylic resins contaminated by Candida Albicans. Conclusion: Concluded that soaking in 0,2% peracetic acid for 5 minutes with microwave irradiation power 840W for 1 minute are effective methods for disinfecting heat-cured acrylic resin, self-cured acrylic resin and microwave-cured acrylic resin, contaminated with Candida Albicans.